Peran Istiá¸¥sÄn Dalam Dinamisasi Pemikiran Hukum Ekonomi Syariah: Peran Istiá¸¥sÄn Dalam Dinamisasi Pemikiran Hukum Ekonomi Syariah - Alimatul Farida; Abu Yasid; Muhammad Lathoif Ghozali (Mu'allim, 2023)
The rapid growth of generations, science and technology raises a variety of new problems that are not only solved by the source of the law of the Koran and hadith. Istiá¸¥sÄn is a way of finding Islamic law which is used as a postulate infiqh Hanafi, although its existence is still being debated among fiqh scholars. This paper aims to examine the roleIstiá¸¥sÄnas a method for discovering Islamic law, particularly in the field of sharia economics. The research approach uses qualitative research with the type of document or text study research, namely, a series of activities related to gathering information relevant to the topic of rolesistiá¸¥sÄn, read, record and process research materials. The research findings in this paper show thatIstiá¸¥sÄn is an important option in determining sharia economic law, such as buying and selling contractsSalam, al-istiá¹£nÄÊ¿, muÊ¿atÄh, online shop and vending machine which can currently be solved by methodIstiá¸¥sÄn,Besides that legal provisions that apply with a basic purposeIstiá¸¥sÄnis eliminatingmadhorot and reach maá¹£lÄá¸¥a.